2022
DOI: 10.1186/s12885-022-09449-9
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis reveals the prognostic and immune infiltration characteristics of glycolysis and hypoxia in head and neck squamous cell carcinoma

Abstract: Background This study aims to construct a new prognostic gene signature in survival prediction and risk stratification for patients with Head and neck squamous cell carcinoma (HNSCC). Method The transcriptome profiling data and hallmark gene sets in the Molecular Signatures Database was used to explore the cancer hallmarks most relevant to the prognosis of HNSCC patients. Differential gene expression analysis, weighted gene co-expression network an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 76 publications
0
9
0
Order By: Relevance
“…Among all the factors, the risk score model in this study has the best predictive ability for both the whole HNSCC cohort and subgroup cohorts. We noted that several pilot reports have identified prognostic models in HNSCC, 35,36 even using glycolysis genes 37,38 . Our work deepens current understanding of the gene set‐based predictions, and provide a more comprehensive and accurate model for the prognostic estimation.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Among all the factors, the risk score model in this study has the best predictive ability for both the whole HNSCC cohort and subgroup cohorts. We noted that several pilot reports have identified prognostic models in HNSCC, 35,36 even using glycolysis genes 37,38 . Our work deepens current understanding of the gene set‐based predictions, and provide a more comprehensive and accurate model for the prognostic estimation.…”
Section: Discussionmentioning
confidence: 66%
“…We noted that several pilot reports have identified prognostic models in HNSCC, 35,36 even using glycolysis genes. 37,38 Our work deepens current understanding of the gene set-based predictions, and provide a more comprehensive and accurate model for the prognostic estimation.…”
Section: Discussionmentioning
confidence: 89%
“…In breast cancer, BASP1 could enhance the anticancer effects of tamoxifen treatment, and patients with high BASP1 were associated with better prognosis (42). Besides, BASP1 upregulation was considered as a high-risk factor in lung adenocarcinoma, cervical cancer, as well as in HNSCC (38,43). Nevertheless, the biological roles and mechanism of BASP1 in regulating HNSCC progression remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxia and acidification of TME are both associated with adverse events and survival after chemoradiotherapy ( 18 ), and animal models have shown that hypoxia is also an essential factor for immune checkpoint inhibitor resistance ( 19 ). According to GEO database analysis, hypoxia and glycolysis are the main risk factors of OS in HNSCC ( 20 ). Multiple studies indicated that hypoxia is one of the drivers of immune suppression ( 18 , 21 ), which can suppress anti-tumor immunity and assist tumors in evading immune surveillance.…”
Section: Tumor Microenvironmentmentioning
confidence: 99%